The Innovation of Glassfiber Reinforced Cement (GRC) Application in Buildings - Mohammad Sahid Indraswara; A. A'isyah; Satriya Wahyu Firmandhani (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2019)
One example of the innovation in building construction that is expansively used at present is Glassfiber Reinforced Cement (GRC). GRC is a cement product based on material mixed with fiberglass. GRC is one of the developments of concrete. This product easily and efficiently provides solutions to a variety of building designs. Additionally, its various forms can be applied to numerous types and functions of buildings. This research aimed to identify the suitability of GRC for several functions. The methods in this study employed a type of qualitative research, with data collection techniques in the form of observation and documentation in several examples of buildings that applied the GRC material innovation. Data analysis was obtained from observation related to GRC types, sizes, installation techniques, and functions in the building. Results showed that the GRC had various types, shapes, and sizes. It could be applied to the building exterior or interior. Each building used different GRC specifications tailored to meet needs and design of the building. GRC installation techniques could use the frame or without frames, adapted to the needs and types of GRC used